EVALUASI KESESUAIAN LAHAN UNTUK PENGEMBANGAN TANAMAN CENGKEH (Eugenia aromatica L) DI DESA MAROWO DAN BONEVOTO KECAMATAN ULUBONGKA KABUPATEN TOJO UNA-UNA - Fudhail, Abdul Kadir Paloloang, Abdul Rahman, Muhammad (AGROTEKBIS, 2016)
This study aims todetermine the suitability ofcroplandclove(Eugenia aromaticaL). inagricultural areasMarowoandBonevotovillage Sub-district of Ulubongka District of Tojo Una-una. The methodusedin this studyis asurvey method. This research wascarried outby means ofsoil samplingin the field, followed by laboratory analysis. Research activitiesincludefour (4) phases: preparation, fieldactivities, climateAnalysis, LaboratoryAnalysisandprocessingof data, map making andpreparation of reports. The results showed thatland suitability classesforthe development ofclove(Eugenia aromaticaL).) In the study areaareasfollows: ClassS3(marginally suitable) contained in theSPLI, II, III, V, VIandIXwith total area of3380,685hectares,which isclassified asN1(currently not suitable) contained in the SPLI,IV, VII, VIII, andXwith an area of2285,168hectaresof land.